Wave packet calculation of cross sections, product state distributions, and branching ratios for the O(1D)+HCl reaction - Piermarini, V; Balint-Kurti, GG; Gray, SK; Gögtas, F; Laganà, A; Hernández, ML (Amer Chemical Soc, 2001)
Time-dependent quantum mechanical calculations have been carried out to estimate the total reactive cross sections, product branching ratios, and product quantum state distributions for the O(D-1) + HCl reaction using both reactant and product Jacobi coordinates. The potential energy surface of T. Martinet et al. (Phys. Chem. Chem. Phys. 2000, 2, 589) has been used in the calculations. The theoretical predictions are compared with experimental results and with the results of classical trajectory calculations on the same surface. The comparisons demonstrate the suitability of the potential energy surface and provide useful insights into the reaction mechanism. The calculations using product Jacobi coordinates are the first calculations for this system which permit the prediction of state-to-state reaction probabilities and of product quantum state distributions.
Keywords: Quantum-Mechanical Calculation; Ab-Initio; Scattering; Dynamics; Hcl; Wavepacket; O((1)D); Hocl